Cruise Tourism in Japanese Coastal Cities: The Role of Revisit and Word-of-Mouth Intentions as Proxies for Behavior - U. Aytun Öztürk (Journal of Tourismology)
This two-wave study was conducted within Japan’s cruise tourism landscape to augment existing research and delve into an understudied area by evaluating the role of destination revisit and word-of-mouth (WOM) intentions as surrogates for self-reported behaviors in inbound tourism. The study employs partial least squares structural equation modeling to analyze data collected in 2018 and 2022, exploring the relationships among overall satisfaction, repeat visitation rate, distance, and revisit and WOM intentions. The analysis of the estimation partition, consisting of 580 valid first-wave responses, helps isolate the critical factors associated with overall satisfaction, such as destination attractiveness, transportation, prices, and tourist attractions and facilities. Based on 77 valid responses gathered in the second wave, which as a sample size has been deemed sufficient for a post-hoc power analysis, the findings significantly reveal that cruise goers’ intentions correlate with self-reported behaviors for revisits and WOM, with intentions explaining 14.4% and 9.3% of the variance observed in the respective behaviors. These results emphasize intentions’ multifaceted role in predicting tourist behavior, underscoring the importance of context-specific constructs in tourism management and unveiling potential pathways for further exploration. The conclusion offers insights that may guide future research and industry practices in crafting strategies to enhance visitor satisfaction and loyalty.